The Japanese grill : from classic yakitori to steak, seafood, and vegetables / Tadashi Ono, Harris Salat - Ono, Tadashi
"American grilling, Japanese flavors: That's the irresistible idea behind The Japanese Grill. In this bold cookbook, chef Tadashi Ono and writer Harris Salat, avid grillers both, share a key insight--that the live-fire cooking we adore here at home marries perfectly with mouthwatering traditional Japanese ingredients like soy sauce and miso. Packed with fast-and-easy recipes, delicious, versatile marinades and